A closer look at the hedonics of everyday meaning and satisfaction. [article]. - Tov, William
Contrasts between eudaimonic well-being and hedonic well-being often compare meaning and happiness. Less work has examined the extent to which meaning and satisfaction can be distinguished. Across 5 diary studies (N = 923) and a large cross-sectional survey (N = 1,471), we examined the affective profile of meaning and satisfaction in everyday life. Using response surface methodology, both judgments were modeled as a joint function of positive (PA) and negative (NA) affect. Affective discrepancy (preponderance of PA over NA) was more strongly associated with satisfaction than meaning. In general, meaning correlated less with affect than satisfaction, but the 2 judgments differ more in their correlation with NA than PA. This implies that people are sometimes able to derive meaning (but not necessarily satisfaction) from negative experiences. We content-coded the events reported by participants for goal directedness, social interactions, and their potential future impact. Interpersonal conflicts and impactful negative events were associated with less satisfaction and meaning at zero-order. However, after controlling for affect and satisfaction, these negative experiences were associated with greater meaning. This effect may reflect additional cognitive processes that enhance meaning but not satisfaction. In all studies, we also observed a positivity dominance effect: At subjectively equivalent levels, PA is weighted more than NA in judgments of meaning and satisfaction. There was no evidence of negativity bias. Results were replicated across different measures and cultural groups (Singapore and the United States). -- (from the authors)